Enhancement of biofuels production by means of co-pyrolysis of Posidonia oceanica (L.) and frying oil wastes: Experimental study and process modeling. (May 2016) - Zaafouri, Kaouther; Ben Hassen Trabelsi, Aida; Krichah, Samah; Ouerghi, Aymen; Aydi, Abdelkarim; Claumann, Carlos Alberto; André Wüst, Zibetti; Naoui, Silm; Bergaoui, Latifa; Hamdi, Moktar
Highlights: Posidonia oceanica and frying oil wastes are promising biomasses for co-pyrolysis. The co-pyrolysis gave a better yield of bio-oil (37 wt.%) at 500 °C. The syngas highest heating value is 20 MJ/kg when H2 /CH4 ratio is 33.16/36.31. The biochar high heating value (19.409 MJ/kg) was obtained for pyrolysis at 500 °C. The decomposition kinetic of solids was validated via linearized Arrhenius model. Abstract: Energy recovery from lignocellulosic solid marine wastes, Posidonia oceanica wastes (POW) with slow pyrolysis responds to the growing trend of alternative energies as well as waste management. Physicochemical, thermogravimetric (TG/DTG) and spectroscopic (FTIR) characterizations of POW were performed. POW were first converted by pyrolysis at different temperatures (450 °C, 500 °C, 550 °C and 600 °C) using a fixed-bed reactor. The obtained products (bio-oil, syngas and bio char) were analyzed. Since the bio-oil yield obtained from POW pyrolysis is low (2 wt.%), waste frying oil (WFO) was added as a co-substrate in order to improve of biofuels production. The co-pyrolysis gave a better yield of liquid organic fraction (37 wt.%) as well as syngas (CH4, H2 …) with a calorific value around 20 MJ/kg. The stoichiometric models of both pyrolysis and co-pyrolysis reactions were performed according to the biomass formula: C α H β O γ N δ S ε . The thermal kinetic decomposition of solids was validated through linearized Arrhenius model.